Adsorption-induced surface normal relaxation of a solid adsorbent - Usenko, A.S. (Condensed Matter Physics, 2016)
We investigate adsorption of a gas on the flat surface of a solid deformable adsorbent taking into account
thermal fluctuations and analyze in detail the effect of thermal fluctuations on the adsorbent deformation in
adsorption. The condition for coexistence of two states of a bistable system of adsorbed particles is derived. We
establish the specific properties of the adsorption-induced surface normal relaxation of an adsorbent caused
by thermal fluctuations. The mean transition times between two stable states of the bistable system are derived
in the parabolic approximation and in the general case. Дослiджено адсорбцiю газу на плоскiй поверхнi твердого адсорбенту, який деформується при адсорбцiї,
враховуючи тепловi флуктуацiї, i детально проаналiзовано вплив теплових флуктуацiй на деформацiю адсорбенту. Отримано умову спiвiснування двох станiв бiстабiльної системи адсорбованих частинок. Встановлено особливостi iндукованою адсорбцiєю нормальної релаксацiї поверхнi адсорбенту, якi обумовленi тепловими флуктуацiями. Знайдено середнi часи переходiв мiж двома стiйкими станами бiстабiльної
системи в параболiчному наближенi i в загальному випадку